Comparison of Accuracy of Point of Care Blood Gas Analysis and Laboratory Analysis in Determining Serum Electrolytes - Nasar, Asad Ahmad; Shoukat, Rafia; Saleem, Safa; Sarfraz, Junaid; Ahmad , Ayesha; Bashir , Faizaan; Qammar, Bilal (Indus Journal of Bioscience Research, 2024)
Objective: The objective was to investigate the correlation and accuracy between sodium and potassium levels measured by point-of-care blood gas analysis and those obtained through laboratory serum analysis. Methods: A prospective observational study was carried out on 70 patients presenting to the Emergency Department of Mayo Hospital Lahore. Paired samples were drawn, one of them was used for point of care (POC) blood gas analysis and the other was sent for serum laboratory analysis under standard techniques. Results: The mean difference between POC blood gas analysis and serum laboratory analysis was 4.9±11.24 (taking 95% CI, p< 0.001) for sodium and 0.94±0.07 (taking 95% CI, p< 0.0001) for potassium. The Pearson correlation coefficient (r) for POC blood gas analysis and serum laboratory analysis was 0.021 for sodium, showing a weak correlation. This suggests that there is minimal linear relationship between the sodium levels measured by the two analyzers. For potassium, Pearson correlation coefficient (r) was found to be 0.939, showing strong correlation. This indicates that while the methods generally agree within this range, some degree of variability is present. Conclusion: The difference between the results obtained from both analyzers was found to be statistically significant and therefore, cannot be used interchangeably.